Studi Gaya Desain Cina Dan Kolonial Pada Furniture Cafe & Bar Shanghai Blue 1920 Di Jakarta - Adelina Kristanti (Intra, 2013)
Before the Europeans and Chinese in Indonesia, the use of the furniture in the small day-to-day life. With the arrival of the Europeans and the Chinese carry considerable influence in which the entry of a new culture began to appear on the forms furnished with stylish design their home country. This design style is created and born from the desire of the authorities to his hometown. Existing furniture in the cafe & bar Blue Shanghai is the Colonial influenced design style (Batavia) and China can be seen from the formation, colors and motifs of the furniture. This research studied the effect of applied and learned Chinese and Colonial style designs on the cafe & bar furniture Shanghai Blue 1920 in Jakarta.